IMPLEMENTASI KAIDAH AL-KHARAJ BI-ADDHAMAN DALAM PEMBIAYAAN SINDIKASI SYARIAH DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH: Implementation Of Al-Kharaj Bi-Addhaman Rules In Sharia Syndicated Financing In The Perspective Of Sharia Economic Law - Mustofa, Nurjamil, Rachmat Syafe’I, (Fakultas Hukum Universitas Komputer Indonesia, 2024)
The goal of this study is to describe the application of the Al-Kharaj Bidhdhaman rule, which specifies who bears the risk and who is entitled to a well-known benefit in sharia business contracts, particularly when applied in syndicated financing carried out by financial institutions as viewed through the lens of sharia economic law. This is a library study that employs qualitative descriptive research methods. Secondary data from books, journals, and other research results are used by researchers to describe the rules in sharia business contracts, also known as legal maxims, and theories about syndicated financing in financial institutions such as banks, which are then normatively analyzed in accordance with laws and regulations. According to the study's findings, the al-Kharaj Bidhdhaman Rule is also a very important rule in syndicated financing-based business activities at Islamic Banks, which is implemented in the agreed clauses in the contract used by customers, bank leaders, and participants of sharia syndicated financing, where the profits obtained by the parties are adjusted to the value of the syndicated participants' capital and the value of the syndicated participants' capital In mudharabah and musharakah-based contracts, the same value is applied for responsibility for the emergence of risks, including losses, which are, of course, excluded if they occur due to force majeure.